Sociopolitical Instability and the Behavior of Savings in Less-Developed Countries - Stewart, Douglas B.; Venieris, Yiannis P. (The Review of Economics and Statistics, 1985)
Douglas B. Stewart, Yiannis P. Venieris, Sociopolitical Instability and the Behavior of Savings in Less-Developed Countries, The Review of Economics and Statistics, Vol. 67, No. 4 (Nov., 1985), pp. 557-563